Issues in adapting supply-chain management (SCM) in construction industry - Abdullah, Che Sobry; Salleh, Dani; Mohtar, Shamimi; Osman, Wan Nadzri (2010)
Construction constitutes an important element in economic development. The economics of the industry primarily to reduce costs and time and thus improve revenues, therefore the component of inputs integration and flow of materials become major perquisite for the industry to remain competitive. Appropriately adoption of Supply-Chain Management (SCM) is a great opportunity for the industry to be more effective and efficient. However, obstacles for SCM in the industry are e.g. the poor level of logistical competence, the partly limited competition, the strong project focus as well as the attitudes and traditions in the construction industry.The industry can learn from the SCM principles and practices.To fulfill the theme of the conference, the discussion of this paper will look into the integration of the supply chain in order to boost efficiency and effectiveness across all supply chain in completing construction projects.Its conclude as SCM should be considered as essential method to the performance and competitiveness of the construction enterprise considering the variety of materials, products and components it requires on each project, the range of subcontracting companies it normally engages, and the variety of consultants it works with.